PP2Cδ Controls the Differentiation and Function of Dendritic Cells Through Regulating the NSD2/mTORC2/ACLY Pathway - Lv, Nianyin; Jin, Sufeng; Liang, Zihao; Wu, Xiaohui; Kang, Yanhua; Su, Lan; Dong, Yeping; Wang, Bingwei; Ma, Tonghui; Shi, Liyun (Frontiers in Immunology, 2022)
Dendritic cells (DCs) are recognized as a key orchestrator of immune response and homeostasis, deregulation of which may lead to autoimmunity such as experimental autoimmune encephalomyelitis (EAE). Herein we show that the phosphatase PP2Cδ played a pivotal role in regulating DC activation and function, as PP2Cδ ablation caused aberrant maturation, activation, and Th1/Th17-priming of DCs, and hence induced onset of exacerbated EAE. Mechanistically, PP2Cδ restrained the expression of the essential subunit of mTORC2, Rictor, primarily through de-phosphorylating and proteasomal degradation of the methyltransferase NSD2 via CRL4DCAF2 E3 ligase. Loss of PP2Cδ in DCs accordingly sustained activation of the Rictor/mTORC2 pathway and boosted glycolytic and mitochondrial metabolism. Consequently, ATP-citrate lyse (ACLY) was increasingly activated and catalyzed acetyl-CoA for expression of the genes compatible with hyperactivated DCs under PP2Cδ deletion. Collectively, our findings demonstrate that PP2Cδ has an essential role in controlling DCs activation and function, which is critical for prevention of autoimmunity.